2013
DOI: 10.4321/s1130-01082013000700003
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory bowel disease patient's satisfaction with healthcare services received: physicians' and nurses' perceptions

Abstract: Background: patient satisfaction with healthcare services provided for inflammatory bowel diseases (IBD) is essential due to high resources use.Objectives: the study aimed to describe patient satisfaction with healthcare services using the CACHE questionnaire and to assess gastroenterologist and nurse perception on patients' satisfaction.Methods: observational multicentric prospective study in 35 Spanish hospitals. Patients included had Crohn's disease or ulcerative colitis. The study was approved by the Hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 15 publications
1
14
1
Order By: Relevance
“…In this large, multicenter survey we used the CACHE questionnaire to measure patient satisfaction in IBD patients undergoing ongoing biologic therapy [13,14]. Among the possible tools, we chose this questionnaire because, compared to other questionnaires such as QUOTE-IBD, patients can complete it more easily and quickly [11,13].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this large, multicenter survey we used the CACHE questionnaire to measure patient satisfaction in IBD patients undergoing ongoing biologic therapy [13,14]. Among the possible tools, we chose this questionnaire because, compared to other questionnaires such as QUOTE-IBD, patients can complete it more easily and quickly [11,13].…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, we found that as many as 19.5% of patients were not satisfied with the IBD information they received through brochures and books, and from healthcare staff. In another study involving 290 Spanish patients with IBD, which used the same questionnaire (CACHE), the patient information score was the lowest (68.5±18) [14]. Likewise, using a different questionnaire (QUOTE-IBD), the received information was judged unsatisfactory by 28% of patients in a previous Italian study performed between April 2010 and February 2011 [22], and by 45% of 162 Dutch IBD patients in 2001 [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These surveys provided information beyond the views of GEs who consider themselves IBD experts -other scientific associations such as ECCO (European Crohn's and Colitis Organization) and GETECCU have already performed surveys (10,11), and drawn interesting conclusions on topics ranging from biosimilar awareness to satisfaction with care. The value of the present survey is likely related to the fact that SEPD includes a large number of gastroenterologists, many of them unrelated to IBD, which will allow "external" but close data on IBD that cannot be obtained from studies by societies devoted to more specific areas of gastroenterology.…”
Section: Discussionmentioning
confidence: 99%